Prognostic value of silent myocardial infarction in patients with chronic kidney disease after kidney transplantation. Issue 4 (12th January 2022) - Santana, Julio C.; Doppalapudi, Harish; Ives, Christopher W.; Farag, Ayman A.; Rizk, Dana V.; Kumar, Vineeta; Iskandrian, Ami E.; Hage, Fadi G.
Abstract : We have shown that silent myocardial infarction (SMI) on 12‐lead ECG is associated with increased cardiovascular disease (CVD) risk in patients awaiting renal transplantation (RT). In this study, we evaluated the prevalence of SMI in patients undergoing RT and their prognostic value after RT. MI was determined by automated analysis of ECG. SMI was defined as ECG evidence of MI without a history of clinical MI (CMI). The primary outcome was a composite of CVD death, non‐fatal MI and coronary revascularization after RT. Of the 1189 patients who underwent RT, a 12‐lead ECG was available in >99%. Of the entire cohort 6% had a history of CMI while 7% had SMI by ECG. During a median follow‐up of 4.6 years, 147 (12%) experienced the primary outcome (8% CVD death, 4% MI, 4% coronary revascularization) and 12% died. Both SMI and CMI were associated with an increased risk of CVD events and all‐cause deaths. In a multivariable adjusted Cox‐regression model, both SMI (adjusted hazard ratio 2.03 [1.25–3.30], p  = .004) and CMI (2.15 [1.24–3.74], p  = .007) were independently associated with the primary outcome. SMI detected by ECG prior to RT is associated with increased risk of CVD events after RT. Abstract : Silent myocardial infarction detected by 12‐lead electrocardiography prior to renal transplantation is associated with increased risk of cardiovascular events after transplantation. Costa and Lentine comments on page 1009 .